The management of chronic liver disease, including transplantation 2 - McCashland, Timothy M. (Henry Stewart Talks, 2021)
Listing criteria for liver transplantation, Management of common medical conditions after liver transplantation, GI related disorders, Bone disease risk, Cardiovascular risk